2006
DOI: 10.1139/b06-131
|View full text |Cite
|
Sign up to set email alerts
|

Proglacial succession of biological soil crusts and vascular plants: biotic interactions in the High Arctic

Abstract: To evaluate the hypothesis that biological soil crusts facilitate the establishment and maintenance of vascular plants during succession, we studied the distribution patterns of crusts and vascular plants along a High Arctic glacier foreland and compared the success of plants growing in and out of crusted substrate. Multivariate analyses determined that distance from the glacier and crust cover were the most important variables, explaining 11% and 9% of the variance in the vegetation data, respectively. Surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 36 publications
2
56
1
Order By: Relevance
“…[13][14][15]. Since the 1960s, numerous field studies have also reported emergent subglacial vegetation; however, all have concluded that the exhumed material was dead (4,5,(16)(17)(18). Here, we present unique field and experimental evidence for the regeneration of subglacial populations of LIA bryophytes collected from the margin of the retreating Teardrop Glacier, and address the important biological implications for polar environments.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…[13][14][15]. Since the 1960s, numerous field studies have also reported emergent subglacial vegetation; however, all have concluded that the exhumed material was dead (4,5,(16)(17)(18). Here, we present unique field and experimental evidence for the regeneration of subglacial populations of LIA bryophytes collected from the margin of the retreating Teardrop Glacier, and address the important biological implications for polar environments.…”
mentioning
confidence: 87%
“…1B). Within the trimline, the vegetation includes both a chronosequence of recolonizing plants and exhumed, intact assemblages of vascular plants and bryophytes (4)(5)(6). The subfossil bryophyte assemblages are in pristine condition, resulting from prior entombment by a nonerosive, cold-based glacier margin, common at high latitudes (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, studies on the long-term changes in macro-organismal diversity have been instrumental in helping ecologists to establish a framework to understand and model successional dynamics (Lockwood et al, 1997;Chase, 2003). For such studies, the use of chronosequences, which assume a space-for-time substitution, despite a few criticisms (for a review see Johnson and Miyanishi, 2008), has offered unique opportunities to investigate soil macro-community development across multiple time scales, in some cases spanning over hundreds of years of (ordered) temporal changes (Bormann and Sidle, 1990;Breen and Lévesque, 2006; reviewed in detail by Walker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have focussed on the functional role of BSCs; however, there is accumulating evidence that BSCs play an important role in both the development and maintenance of vascular plant communities in arctic environments (Breen & Levesque, 2006;Gold et al, 2001). BSCs tend to increase the N content, as well as, the uptake of Cu, K, Mg and Zn of associated seed plants (Belnap & Harper, 1995;Harper & Belnap, 2001).…”
Section: Biological Soil Crustsmentioning
confidence: 99%